Development of Islamic Study Practices in the Digital Era: A Case Study on Qur'an Learning with Artificial Intelligence (AI) - Sofiatun Anisa Anisa (International Tatho Academics, 2026)
This community service research aims to examine the effectiveness of implementing the Ngaji artificial intelligence (AI) application at Taman Pendidikan al-Qur’an (TPQ) Birul Walidain in Pekalongan. A pre-experimental design with pre- and post-tests was applied to 20 students aged 10–13 years, using a structured knowledge assessment instrument analyzed descriptively and quantitatively. The results showed significant improvements across all indicators: basic AI understanding increased from 55% to 100% (+45 percentage points), awareness of learning enhancement aspects increased from 20% to 100% (+80 percentage points), and understanding of AI benefits increased from 55% to 75%, with an average cross-indicator increase of ±37.5 percentage points. These findings contribute empirically to the discourse on edupreneurship by demonstrating that an AI-integrated learning model can be effectively implemented in TPQs, while also offering a replicable framework for the modernization of non-formal Islamic education based on digital literacy.